Signal competition versus metabolic inhibition: Divergent fates of antibiotic resistance genes under N-acyl-L-homoserine lactone-targeted quorum quenching in composting - Ruohan Xia; Tong Shi; Jirong Zhao; Guoxue Li; Wenhai Luo; Zhicheng Xu (Journal of Hazardous Materials, 2026)

MnO₂ polymorphs direct the selective degradation of fluoroquinolone antibiotics: Insights from adsorption, oxidation, and O₂ activation mechanisms - Ruohan Zhao; Enhui Wu; Xiangyu Zhu; Xinfei Ge; Xin Xiao; Baoliang Chen (Chemical Engineering Journal, 2026)

Chemical reaction kinetics regulated dual-signal sensing system for discriminating EV-A71 and CV-A16 - Tongtong Ye; Wenjing Xu; Ruohan Tang; Yuhan Wang; Yang Li; Xuming Zhao; Hui Zhang; Lihua Chen (Analytica Chimica Acta, 2026)

Construction of electrochemical dual‑carbon-membrane reactor with nitrogen-doped carbon membranes for synergetic dimethylacetamide degradation and ion removal via capacitive deionization: Insights into proton exchange membrane-mediated charge compensation and operational stability - Yuxuan Zhu; Hanlin Wang; Ruohan Wang; Haikuo Lei; Heli Zhao; Huichao Su (Chemical Engineering Journal, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Effects of microsized and nanosized polystyrene on detrital processing and nutrient dynamics in streams - Jingjing Du; Mengxi Gao; Zhi Rao; Xun Zhou; Yan Su; Jianguo Zhao; Jianxiang Lv; Ruohan Mao; Yuran Song; Xia Cao (Environmental Pollution, 2026)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

First retrieval of 24-hourly 1-km-resolution gapless surface ozone (O3) from space in China using artificial intelligence: Diurnal variations and implications for air quality and phytotoxicity - Fan Cheng; Zhanqing Li; Zeyu Yang; Ruohan Li; Dongdong Wang; Aolin Jia; Ke Li; Bin Zhao; Shuxiao Wang; Dejia Yin; Shengyue Li; Wenhao Xue; et al. (Remote Sensing of Environment, 2025)

The impact of cryosphere service change on the social-ecological systems resilience: Evidence from the Qilian Mountains Area in China - Di Zhao; Jia Chen; Xiaowen Zhang; Ruohan Shi; Yang Xiao; Ziyan Chen (Journal of Environmental Management, 2024)

Hyaluronic acid modulates gut microbiota and metabolites relieving inflammation: A molecular weight-dependent study - Chuan Zhang; Botao Wang; Leilei Yu; Ruohan Zhao; Qingsong Zhang; Chengcheng Zhang; Shumao Cui; Jianxin Zhao; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Science Bulletin, 2024)

Research on precise phenotype identification and growth prediction of lettuce based on deep learning - Haiye Yu; Mo Dong; Ruohan Zhao; Lei Zhang; Yuanyuan Sui (Environmental Research, 2024)

Operation-friendly and accurate naked-eye observation assay for fast zoonotic echinococcosis and pulmonary tuberculosis monitoring in clinics - Hong Liang; Ruohan Wang; Tianying Luo; Mengying Yuan; Xia He; Rongrong Jin; Yangyang Zhao; Rongsheng Tong; Yu Nie (Analytica Chimica Acta, 2024)

Bacteriostatic mechanism of Lactiplantibacillus plantarum CS3 cell-free supernatant of on soy sauce spoilage bacteria - Shuyu Zhang; Ruohan Yao; Qifeng Wang; Wenjun Wang; Shuoshuo Zhao; Hao Wang; Ling Zhu; Yunping Yao; Guozhong Zhao (Food Bioscience, 2024)

Shaking table tests on deformation pattern and failure mechanism of fault-crossing tunnels in non-rupture scenario - Ruohan Li; Xu Zhao; Emilio Bilotta; Jinghua Zhang; Mi Zhao; Jingqi Huang; Yong Yuan (Soil Dynamics and Earthquake Engineering, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Identification of novel umami peptides from yeast extract and the mechanism against T1R1/T1R3 - Hao Wang; Wenjun Wang; Shuyu Zhang; Zhenhao Hu; Ruohan Yao; Hadiatullah Hadiatullah; Pei Li; Guozhong Zhao (Food Chemistry, 2023)

A critical review on selenium removal capacity from water using emerging non-conventional biosorbents - Habib Ullah; Baoliang Chen; Audil Rashid; Ruohan Zhao; Asfandyar Shahab; Guo Yu; Ming Hung Wong; Sangar Khan (Environmental Pollution, 2023)

Adsorption and photocatalytic degradation of quinolone antibiotics from wastewater using functionalized biochar - Ning Cheng; Bing Wang; Miao Chen; Qianwei Feng; Xueyang Zhang; Shengsen Wang; Ruohan Zhao; Tao Jiang (Environmental Pollution, 2023)

Calcium alginate-nZVI-biochar for removal of Pb/Zn/Cd in water: Insights into governing mechanisms and performance - Ruohan Zhao; Bing Wang; Pan Wu; Qianwei Feng; Miao Chen; Xueyang Zhang; Shengsen Wang (Science of The Total Environment, 2023)

Anisotropic In-Plane strain engineering Ni(OH)2 to activate alkaline hydrogen evolution reaction - Wenda Zhong; Ruohan Yu; Weilong Cao; Le Sun; Yi Yang; Ingo Manke; Chao Yang; Kangning Zhao (Chemical Engineering Journal, 2023)

Corrigendum to SaMT3 in Sedum alfredii drives Cd detoxification by chelation and ROS-scavenging via Cys residues [Environmental Pollution 315 (2022) 120410] - Jianqi Zhao; Ruohan Xie; Jiayu Lin; Lingling Xu; Xiaoyu Gao; Xianyong Lin; Shengke Tian; Lingli Lu (Environmental Pollution, 2023)

In vitro fermentation of heparin by the human gut microbiota: Changes in the microbiota community and metabolic functions - Chuan Zhang; Leilei Yu; Qixiao Zhai; Ruohan Zhao; Jianxin Zhao; Hao Zhang; Wei Chen; Fengwei Tian (Food Chemistry, 2023)

Recovery of nitrogen and phosphorus in wastewater by red mud-modified biochar and its potential application - Zhipeng Zhao; Bing Wang; Qianwei Feng; Miao Chen; Xueyang Zhang; Ruohan Zhao (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Mechanisms of cancer cell death induction by paclitaxel: an updated review - Shuang Zhao; Yufei Tang; Ruohan Wang; Masoud Najafi (Apoptosis, 2022)

Constant hypoxia inhibits osteoclast differentiation and bone resorption by regulating phosphorylation of JNK and IκBα - Zhenzhen Ma; Ruohan Yu; Jinxia Zhao; Lin Sun; Leilei Jian; Changhong Li; Xiangyuan Liu (Inflammation Research, 2019)